Multiple modernities and postsecular societies - Rosati, Massimo; Stoeckl, Kristina (Global connections, 2012)
Engaging with the idea that the world reveals not one, but many routes to modernity, this volume explores the role of religion in the emergence of multiple forms of modernity, which evolve according to specific cultural conditions and interpretations of the `modern project`. Drawing upon case study material from Africa, The Middle East, Russia and South America, it examines the question of whether modernity, democracy and secularism are universalistic concepts or are, on the contrary, unique to Western civilization, whilst considering the relationship of postsecularism to the varied paths of modern development